2019
DOI: 10.3390/su11061792
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Asphalt Mixtures Modified with Ground Tire Rubber Modifiers and Recycled Materials

Abstract: The usage of Ground Tire Rubber (GTR) in asphalt pavements has gained renewed interest due to its potential sustainability, economic, and performance benefits. This study focuses on asphalt mixtures designed with three different rubber modifier products including (1) a terminal-blend GTR, (2) a dry-process, chemically processed rubber product, and (3) a terminal-blend rubber-polymer hybrid product. The modifications were incorporated into Illinois Tollway’s approved Stone Matrix Asphalt (SMA) designs using (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…The extension of this approach to modern, heterogeneous mixtures with RAP, GTR, and other components/additives is suggested by the results obtained in this study as well as others studies (Buttlar et al, 2019;Rath et al, 2019;Buttlar and Wang, 2016 slightly lower design air void level for high ABR mixes, perhaps 3.0 or 3.5%, applying this principle for mixtures containing both RAP and RAS.…”
Section: Dc(t) Fracture Test Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The extension of this approach to modern, heterogeneous mixtures with RAP, GTR, and other components/additives is suggested by the results obtained in this study as well as others studies (Buttlar et al, 2019;Rath et al, 2019;Buttlar and Wang, 2016 slightly lower design air void level for high ABR mixes, perhaps 3.0 or 3.5%, applying this principle for mixtures containing both RAP and RAS.…”
Section: Dc(t) Fracture Test Resultssupporting
confidence: 66%
“…According to Brock (1998), a savings of $1 billion dollars annually could be realized by engineering RAS into asphalt mixtures in a comprehensive manner (Brock, 1998). Owing to the regional use of RAS worldwide (most prevalent in the Midwest and East Coast United States Rath et al, 2019;Williams et al, 2018;Buttlar and Wang, 2016)), somewhat limited research and field data regarding RAS are available compared to research on RAP.…”
Section: Introductionmentioning
confidence: 99%
“…The application of reclaimed asphalt pavement (RAP) in asphalt mixtures has been vigorously encouraged and promoted over the past decades due to the desirable environmental benefit, along with the cost reduction [1][2][3][4]. The use of RAP has been promoted from low-value use (as unbound layer materials [5], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt has been widely used in airfield and high-grade road pavement due to its numerous advantages such as smoothness, low-vibration, high-automated construction, and easy maintenance [1][2][3][4]. Worldwide, annually, over 86 million tons of asphalt binder is combined with gravel or sand to pave roads [5][6][7]. However, it has been observed that the production of asphalt requires a major expenditure of natural resources, and the associated mining, refining, production, and construction produce considerable greenhouse gas emissions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%